Chitosan as a biomaterial for the prevention and treatment of dental caries: antibacterial effect, biomimetic mineralization, and drug delivery - Qu, Shanlin; Ma, Xiaolin; Yu, Shuo; Wang, Rui (Frontiers in Bioengineering and Biotechnology, 2023)
Dental caries is a chronic, progressive disease caused by plaque, influenced by multiple factors and can damage the hard tissues of the teeth. It can lead to the onset and development of other oral diseases, seriously affecting patients' quality of life. The creation of effective biomaterials for the prevention and treatment of dental caries has become one of the relentless goals of many researchers, with a focus on inhibiting the production of cariogenic plaque and retaining beneficial bacteria, guiding and promoting the reconstruction of dental hard tissues, and delaying the progression of existing caries. Chitosan is a natural cationic polymer extracted from the shells of crustaceans and shellfish. Since its discovery, chitosan has shown to have various biological functions such as antibacterial, biomimetic mineralization, drug delivery, etc., making it one of the most promising biopolymers for new caries prevention and materials of prostheses. Therefore, this article provides an overview of the anti-caries applications of chitosan, which mainly covers the basic research on the application of chitosan in caries prevention and treatment since 2010, with a focus on categorizing and summarizing the following characteristics of chitosan as a caries prevention material, including its antibacterial effect, biomimetic mineralization effect and delivery ability of caries prevention drugs and vaccines. It also explores the limitations of current research on chitosan as a caries prevention biomaterial and the difficulties that need to be focused on and overcome in the future to provide theoretical reference for the clinical implementation of chitosan as a caries prevention biomaterial.